Pelestarian Kebudayaan Gorontalo Melalui Pelatihan Bagi Siswa SD-SMP SATAP Tibawa, Kabupaten Gorontalo - Ronal Hutagalung; Aang Panji Permana; Muhammad Kasim (Univeristas Negeri Gorontalo, 2022)
The preservation of the Gorontalo regional culture, both folk dances and folk songs, is very necessary. One form of cultural preservation is through training for elementary and junior high school students. The target of this activity is students of SDN 17 and SMPN 12 SATAP, Tibawa District, Gorontalo Regency. The selection of elementary and junior high school students is in accordance with the training objectives to provide students with information about Gorontalo culture and customs and to train students' self-confidence to appear in public. The results achieved from the Gorontalo regional cultural training, both folk dances and folk songs for students were successful and as expected. The intended result is that the students succeeded in showing their appearance in performing arts events and gaining new knowledge about Gorontalo culture.